1997
DOI: 10.1046/j.1365-2265.1997.2361058.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive amino‐terminal pro‐brain natriuretic peptide (NT‐PROBNP): a new marker of cardiac impairment

Abstract: Plasma levels of immunoreactive amino terminal-proBNP are raised in cardiac impairment, including NYHA Class I, and rise with increasing cardiac decompensation. Metabolism and tissue uptake of immunoreactive amino terminal-proBNP and immunoreactive BNP-32 appear similar. In cardiac impairment the proportional and absolute increment above normal levels of the aminoterminal BNP peptide exceeds that for BNP-32 and suggest that amino terminal-proBNP may be a more discerning marker of early cardiac dysfunction than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
341
11
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(388 citation statements)
references
References 30 publications
27
341
11
9
Order By: Relevance
“…ProBNP has therefore been suggested as an even better marker of heart failure than BNP. [21][22][23][24] A few previous studies have reported increased plasma BNP concentrations in patients with cirrhosis. [15][16][17][18][19][20] The natriuretic peptides are synthesised as pre-prohormones with endocrinologically active C terminal peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ProBNP has therefore been suggested as an even better marker of heart failure than BNP. [21][22][23][24] A few previous studies have reported increased plasma BNP concentrations in patients with cirrhosis. [15][16][17][18][19][20] The natriuretic peptides are synthesised as pre-prohormones with endocrinologically active C terminal peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, the propeptide of brain natriuretic peptide (proBNP) has been suggested as an even better indicator of early cardiac dysfunction. [21][22][23][24] Until now, no study has assessed concentrations of circulating proBNP in patients with cirrhosis. The present study was therefore undertaken to determine concentrations of circulating proBNP and BNP in patients with cirrhosis.…”
mentioning
confidence: 99%
“…Plasma was separated within 20 min by centrifugation and stored at À 80 1C. Plasma was assayed for atrial natriuretic peptide (ANP), 13 N-terminal ANP (NT-proANP), 14 B-type natriuretic peptide (BNP), 15 N-terminal B-type natriuretic peptide (NT-proBNP), 16 C-type natriuretic pepetide (CNP) 17 and cyclic guanosine monophosphate (cGMP). 18 Transthoracic echocardiography was performed using a GE Vivid 3 ultrasound system (GE Medical Systems, Waukesha, WI, USA) at Christchurch Hospital and an ATL HDI 5000 (Philips Healthcare, Andover, MA, USA) at Auckland City Hospital.…”
Section: Coronary Disease Cohortmentioning
confidence: 99%
“…The cleavage of pro-BNP within the heart results in two components produced in equal amounts: BNP 32 (the active hormone) and N-terminal (NT) pro-BNP (the inactive fragment) (12). The plasma half-life of NT pro-BNP is approximately 2 h in comparison with that of BNP 32 (20 min) (13), which explains the higher level of NT pro-BNP in myocardial dysfunction (14).In addition to the documented relationship between BNP and myocardial dysfunction mentioned above, there are other conditions associated with increased BNP level that include primary pulmonary hypertension, myocarditis, cardiac allograft rejection, arrhythmogenic right ventricle with decreased LV ejection fraction (EF), renal failure, Kawasaki disease, ascitic cirrhosis and endocrine diseases (Cushing's syndrome, primary hyperaldosteronism) (8). Other patient characteristics that may influence the BNP level, independent of disease, are advancing age, probably reflecting LV subclinical abnormalities (15) and female sex, both of which result in increased BNP level (15,16).…”
mentioning
confidence: 99%
“…The cleavage of pro-BNP within the heart results in two components produced in equal amounts: BNP 32 (the active hormone) and N-terminal (NT) pro-BNP (the inactive fragment) (12). The plasma half-life of NT pro-BNP is approximately 2 h in comparison with that of BNP 32 (20 min) (13), which explains the higher level of NT pro-BNP in myocardial dysfunction (14).…”
mentioning
confidence: 99%